PELUANG IKATAN DAI MUDA INDONESIA (IDMI) DALAM MEMBINA MASYARAKAT MUSLIM DI KOTA PALU - Mahmud, Muchlis A (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 14 No 1 (2018)DO - 10.24239/al-mishbah.Vol14.Iss1.106, 2018)
This article discusses the dakwah method of the Indonesian Young Dai Association (IDMI) of Palu in fostering and developing the religiosity aspects of the community of Palu. Coaching is carried out to its members as well as to the general public. In carrying out its missionary activities, IDMI applied a variety of methods in fostering Muslim communities through recitation groups that were held regularly, ta’līm assemblies for women, as well as recitals held at the commemoration of Islamic holidays. Observation of da`wah activities and interviews with the preachers affiliated with IDMI showed that this institution had an excellent opportunity in carrying out community religious development in Palu. The enthusiasm of the community to take part in the recitations organized by IDMI and the dakwah material that is inclusive provides the possibility for this institution to act as a unifying node in the heterogeneous community of Palu.